Photochromic polyhydroxyalkanoate / polylactic acid fiber as well as preparation method and application thereof
By physically combining PHA with PLA and adding photochromic materials to the core layer, photochromic PHA/PLA fibers with a leather core structure were prepared, which solved the brittleness and molding difficulties of PHA fibers during the preparation process, and achieved the improvement of the mechanical properties of the fibers and the effect of reversible discoloration.
Patent Information
- Application Number
- CN202411854451.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing polyhydroxy fatty acid ester (PHA) fibers have brittle problems during the preparation process, low nucleation density, slow crystal growth, and sensitivity to temperature conditions, which increases the difficulty of melt spinning processing.
Photochromic PHA/PLA fibers with a skin-core structure were prepared by physically combining PHA with a non-toxic and harmless biodegradable material polylactic acid (PLA), and adding inorganic-organic hybrid photochromic materials based on the principle of photobleaching to the core layer. The spinning is performed using a microfluidic device to regulate the rotation speed of the fiber collector and the propulsion rate of the propulsion pump, and improve the strength and elongation of the fiber breakage.
It has achieved improved mechanical properties of PHA fibers, excellent biocompatibility, biodegradability and transparency, and achieved reversible discoloration under visible light, expanding the application field of PHA fibers.
Smart Images

Figure CN119753885A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyhydroxyalkanoate fibers, and in particular to a photochromic polyhydroxyalkanoate / polylactic acid fiber and a preparation method and application thereof. Background Art
[0002] With the rapid development of society and technology, smart photochromic (PC) fabrics, as a high value-added smart product, have broad application prospects in the fields of textiles, military equipment, anti-counterfeiting, etc. Inorganic-organic PC materials, as representatives of the new generation of PC materials, achieve the dual goals of rapid color switching and extended reversible cyclability by cleverly combining the advantages of inorganic and organic materials, providing new ideas and methods for the preparation of smart photochromic fabrics.
[0003] In the process of preparing smart photochromic fabrics, incorporating photochromic materials into polymer fibers has become a mainstream technology. However, with the increasing global awareness of ecological protection, traditional polymer raw materials face challenges due to their non-renewable nature and environmental pollution. Polyhydroxyalkanoates (PHA), as a biodegradable polymer material derived from renewable resources, have excellent biocompatibility and biodegradability. PHA not only gets rid of dependence on fossil raw materials, but also shows broad application potential in many fields such as biology, medicine, plastics, and packaging.
[0004] Although PHA has achieved remarkable research results in many fields, its research and application in the textile field are still relatively lagging behind. This is mainly due to the brittleness of PHA fibers during the preparation process, as well as the difficulty in fiber molding caused by the low nucleation density and slow crystal growth of conventional PHA. In order to overcome these difficulties, researchers have tried to prepare PHA blended fibers by blending modification to improve their spinnability and fiber properties. However, existing PHA fiber preparation methods, such as the polyhydroxyalkanoate fiber preparation process disclosed in CN102108563A, have problems such as long crystallization time, coarse fiber diameter and high cost, which limit the widespread application of PHA fibers.
[0005] In addition, there are many challenges in the melt spinning process of PHA. Since the melting temperature of PHA is close to the thermal degradation temperature, PHA is highly sensitive to temperature conditions, which greatly increases the difficulty of melt spinning processing and forming. During the melt spinning process, the spinnability of raw materials varies greatly, decomposition is easy to occur under high temperature conditions, and the filaments solidify slowly and are easy to stick together, which further increases the difficulty of PHA fiber preparation. Although the addition of additives such as plasticizers and nucleating agents can improve these problems to a certain extent, these additives often affect the biocompatibility and biodegradability of PHA, while increasing the cost of the final product.
[0006] Therefore, how to improve the spinnability and fiber properties of PHA fibers while maintaining the biocompatibility and biodegradability of PHA has become an urgent technical problem to be solved. Summary of the Invention
[0007] To solve the above technical problems, the object of the present invention is to provide a photochromic polyhydroxyalkanoate / polylactic acid fiber, its preparation method and application.
[0008] The above object of the present invention is achieved by the following technical solutions:
[0009] The present invention provides a photochromic polyhydroxyalkanoate / polylactic acid fiber, and the photochromic polyhydroxyalkanoate / polylactic acid fiber has a core-shell structure. The core layer material includes a high molecular polymer, a dye and SnO 2-x , where 0 < x < 0.5, and the high molecular polymer is polyvinyl alcohol (PVA) and / or cellulose; the skin layer material includes polyhydroxyalkanoate (PHA) and polylactic acid (PLA).
[0010] The present invention physically combines PHA with the non-toxic and harmless biodegradable material PLA, improves the mechanical properties of PHA fibers, increases their strength and elongation at break, and makes PHA / PLA fibers have excellent biocompatibility and biodegradability. An inorganic-organic hybrid photochromic material based on the principle of photo-bleaching is added to the core layer of PHA / PLA fibers, making PHA / PLA fibers sensitive to visible light. By adding different redox dyes, color changes such as blue, green, red, and purple can be achieved, and reversible color change can occur under visible light.
[0011] Further, the molecular weight of the high molecular polymer is 70,000 - 80,000.
[0012] Further, the dye is selected from one or more of methylene blue (MB), methylene green (MG), and neutral red (NR).
[0013] The present invention combines the photoreduction activity of semiconductor nanoparticles as photocatalysts and redox-mediated color-switching dyes as color components, such as MB, MG, and NR. Mixing three color systems can produce full-color inks.
[0014] Further, the mass ratio of the polyhydroxyalkanoate to the polylactic acid is (5 - 20):(100 - 120).
[0015] The present invention provides a microfluidic device, including:
[0016] An internal phase propulsion pump for propelling the internal phase solution;
[0017] An external phase propulsion pump for propelling the external phase solution;
[0018] Slide
[0019] Dispensing needle, which is located at the port of the outer-phase capillary far from the fiber collector and is used to connect the inner-phase capillary and the outer-phase capillary;
[0020] Inner-phase capillary, part of which is embedded inside the outer-phase capillary and is used to transport the inner-phase solution;
[0021] Outer-phase capillary, which is fixed on the surface of the slide and is used to transport the outer-phase solution; and
[0022] Fiber collector, which is used to collect the fibers formed after the interaction between the inner-phase solution and the outer-phase solution.
[0023] Wherein, the slide, the dispensing needle, the inner-phase capillary and the outer-phase capillary form a microfluidic chip.
[0024] The present invention provides a method for preparing photochromic polyhydroxyalkanoate / polylactic acid fibers. The above microfluidic device is used to prepare photochromic polyhydroxyalkanoate / polylactic acid fibers, which includes the following steps:
[0025] Dissolve the core layer material in a solvent to obtain an inner-phase solution. The core layer material includes a polymer, a dye and SnO 2-x , wherein, 0 < x < 0.5, and the polymer is polyvinyl alcohol and / or cellulose; mix the polyhydroxyalkanoate solution and the polylactic acid solution to obtain an outer-phase solution; use an inner-phase propulsion pump to push the inner-phase solution into the inner-phase capillary, and use an outer-phase propulsion pump to push the outer-phase solution through the dispensing needle into the outer-phase capillary. The fiber collector is filled with a coagulation bath, and the photochromic polyhydroxyalkanoate / polylactic acid fibers are collected in the coagulation bath.
[0026] In the preparation method provided by the present invention, a large number of hydroxyl groups are contained on the cellulose molecular chain, and these hydroxyl groups can form hydrogen bonds or other chemical bonds with the active groups on the surface of the inorganic photochromic material SnO 2-x , so as to achieve a firm combination between the two, which is beneficial to improving the stability of the composite material; the mixed solution of PHA and PLA can diffuse and volatilize in the coagulation bath to form microfibers with uniform size. Moreover, by adjusting the microfluidic spinning parameters, the fibers can have a certain strength and elongation at break, so as to have a wider application prospect. The preparation method provided by the present invention is simple and has a low cost. By using a controllable, reliable, safe and low-cost microfluidic spinning method, single fibers can be continuously manufactured, and the composition and microstructure of the single fibers can be adjusted.
[0027] Furthermore, the solvent is water.
[0028] Furthermore, the concentration of the polymer in the inner phase solution is 10-17 wt %, the concentration of the dye in the inner phase solution is 0.01-0.05 M, and the concentration of SnO in the inner phase solution is 0.01-0.05 M. 2-x The concentration is 30-100 mg / mL.
[0029] Furthermore, the volume ratio of the polyhydroxyalkanoate solution to the polylactic acid solution is (1-3):5.
[0030] Furthermore, the concentration of polyhydroxyalkanoate in the polyhydroxyalkanoate solution is 5-10 wt %, and the concentration of polylactic acid in the polylactic acid solution is 15-25 wt %.
[0031] Furthermore, the propulsion rate of the inner phase propulsion pump is 3-5 mL / h.
[0032] Furthermore, the propulsion rate of the external phase propulsion pump is 3-5 mL / h.
[0033] Furthermore, the collection rotation speed of the fiber collector is 2-4r / min.
[0034] Furthermore, the coagulation bath is polyethylene glycol and / or ethanol, and the polyethylene glycol is preferably polyethylene glycol 400 (PEG 400).
[0035] The present invention also protects the application of the photochromic polyhydroxyalkanoate / polylactic acid fiber in the field of textiles.
[0036] Beneficial effects of the present invention:
[0037] 1. In the present invention, PHA and PLA are blended and spun to obtain PHA / PLA fibers which have certain strength and elongation at break, and have excellent biocompatibility, biodegradability and transparency.
[0038] 2. The present invention expands the application field of PHA fiber, combines PHA / PLA with photochromic materials, uses PHA / PLA as the skin material, dyes, high molecular polymers and SnO 2-x As the core material, skin-core structured fibers were prepared by microfluidics. The PHA / PLA fibers can achieve reversible color change under visible light irradiation.
[0039] 3. Since the thermal processing window of PHA is relatively narrow, wet spinning can replace melt spinning to avoid thermal degradation. The present invention uses a temporary and simplified spinning device, which is easy to operate and is superior to the wet spinning machine used in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of the microfluidic device of the present invention.
[0041] Figure 2 The morphology characterization diagrams of the photochromic PHA / PLA fibers prepared in Example 1; wherein (a) is a surface scanning electron microscope (SEM) image, (b) is a local enlarged image of (a), (c) is a cross-sectional SEM image, and (d) is an optical microscope (OM) image.
[0042] Figure 3 The actual pictures are of the photochromic PHA / PLA fibers prepared in Examples 1 and 9-13.
[0043] Figure 4 The stress-strain curves of PLA fiber, photochromic PHA / PLA fiber prepared in Example 1 and Example 4 are shown.
[0044] Figure 5 The stress-strain curves of the photochromic PHA / PLA fibers prepared in Example 1 and Examples 5-8 are as follows; (a) is Example 1 (22% PLA), Example 5 (20% PLA) and Example 6 (24% PLA), and (b) is Example 1 (4 r / min), Example 7 (2.4 r / min) and Example 8 (3 r / min).
[0045] Figure 6 The test results of the photochromic PHA / PLA fiber prepared in Example 1 under blue light irradiation are shown in Figure 1; (a) is a real picture of the fiber gradually fading under different irradiation times; (b) is a K / S curve, and (c) is a CIE chromaticity diagram (the irradiation times in the direction of the arrows are 0, 5, 10, 15, 20, and 30 s, respectively).
[0046] Figure 7 The test results of the photochromic PHA / PLA fiber prepared in Example 2 under blue light irradiation are shown in Figure 2; (a) is a real picture of the gradual fading under different irradiation times; (b) is a K / S curve, and (c) is a CIE chromaticity diagram (the irradiation times in the direction of the arrows are 0, 5, 10, 15, and 20 s, respectively).
[0047] Figure 8 The test results of the photochromic PHA / PLA fiber prepared in Example 3 under blue light irradiation are shown in Figure 3; (a) is a real picture of the gradual fading under different irradiation times; (b) is a K / S curve diagram, and (c) is a CIE chromaticity diagram (the irradiation times in the direction of the arrows are 0, 5, 10, and 15 seconds, respectively).
[0048] Fig. 9 This is a real picture of the sample made of photochromic PHA / PLA fiber prepared in Example 1, which fades under blue light (400-480nm) and recolors under red light (625-665nm).
[0049] Fig.10 The figures are test results of the inner phase solution in Example 15 under light irradiation; wherein, (a) is a real picture of the inner phase solution fading under green light (500-550nm) and recoloring under red light (625-665nm), (b) is a UV absorption spectrum of the inner phase solution, and (c) is a graph showing the change in absorption intensity at 662nm after 10 cycles of alternating irradiation with UV light (365nm) and red light.
[0050] Explanation of the reference numerals: 1. inner phase propulsion pump, 2. outer phase propulsion pump, 3. glass slide, 4. dispensing needle, 5. inner phase capillary, 6. outer phase capillary, 7. fiber collector. DETAILED DESCRIPTION
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0052] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0053] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0054] The present invention provides a microfluidic device, such as Figure 1 As shown, including:
[0055] An internal phase propulsion pump 1, used for propulsing the internal phase solution;
[0056] An external phase propulsion pump 2, used for propulsing the external phase solution;
[0057] Slide 3;
[0058] A dispensing needle 4, which is located at the end of the external phase capillary tube away from the fiber collector and is used to connect the internal phase capillary tube and the external phase capillary tube;
[0059] An inner phase capillary 5, part of which is embedded in the outer phase capillary and is used to transport the inner phase solution;
[0060] an external phase capillary 6 fixed on the surface of the glass slide for transporting the external phase solution; and a fiber collector 7 for collecting fibers formed after the internal phase solution and the external phase solution interact with each other.
[0061] In the following examples, the self-doped SnO was synthesized by hydrothermal method. 2-x The nanopowder was prepared as follows: 0.96 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), 53.3 mL of N, N-dimethylacetamide (DMAC) and 10.7 mL of deionized water were mixed at room temperature, and then 0.24 g of tin powder (Sn) and 2.81 g of crystalline tin tetrachloride (SnCl4·5H2O) were added under vigorous stirring, and stirred for 1 h to obtain a mixed solution. The mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 180 ° C for 4 h. The precipitate obtained by the reaction was washed three times with distilled water, dried, and ground to obtain SnO 2-x Nano powder.
[0062] The molecular weight of PVA in the following examples is 74885.
[0063] Example 1
[0064] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber comprises the following steps:
[0065] (1) SnO 2-x The nanopowder was added to deionized water and dried to prepare a SnO solution with a concentration of 40 mg / mL. 2-x Dispersion, add 40mL of dispersion to a blue-capped bottle, add 6.5g of PVA, stir magnetically in a water bath at 95°C for 4h, add 1.6mL of MB solution (concentration in the internal phase solution is 0.01M) after cooling, stir magnetically for 2h at room temperature, let stand to defoam, and obtain a uniform internal phase solution. Dissolve 6g of PHA in 94g of chloroform (CF) to obtain a PHA solution, dissolve 22g of PLA in 78g of dichloromethane (DCM) to obtain a PLA solution, and mix the PHA solution and the PLA solution in a volume ratio of 2:5 to obtain an external phase solution.
[0066] (2) Build a microfluidic device. The inner phase circular tube capillary is embedded in the outer phase square capillary, the outer phase square capillary is fixed on the surface of the slide, and then the joint close to the inner phase circular tube capillary is sealed with a dispensing needle to form a microchannel. The inner diameter of the inner phase circular tube capillary is 0.5 mm, and the inner diameter of the outer phase square capillary is 1 mm. The inner phase solution and the outer phase solution in step (1) are respectively loaded into two syringes, and the syringes are installed on the propulsion pump. The inner phase propulsion pump and the inner phase capillary are connected with a polytetrafluoroethylene tube, and the outer phase propulsion pump and the dispensing needle are connected with a polytetrafluoroethylene tube. The port of the outer phase capillary away from the inner phase capillary is immersed in the PEG 400 coagulation bath of the fiber collector, wherein the propulsion rate of the inner phase propulsion pump is 3 mL / h, the propulsion rate of the outer phase propulsion pump is 3 mL / h, and the collection speed of the fiber collector is 4r / min. The fibers collected from the coagulation bath were washed three times with deionized water and air-dried to obtain photochromic PHA / PLA fibers.
[0067] The morphology of the photochromic PHA / PLA fibers prepared in Example 1 is as follows: Figure 2 As shown, the skin layer of the photochromic PHA / PLA fiber is transparent, which does not affect the color change of the core layer, and can achieve the effect of ecological protection and protecting the internal phase fluid state to extend the service life.
[0068] Example 2
[0069] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that in Example 1, except that: in step (1), SnO 2-x The nanopowder was added to deionized water and dried to prepare a SnO solution with a concentration of 40 mg / mL. 2-x Dispersion liquid, add 30mL dispersion liquid and 10mL deionized water in a blue-capped bottle, and add 6.5g PVA and magnetically stir in a water bath at 95℃ for 4h. After cooling, add 1.6mL MB solution (the concentration in the internal phase solution is 0.01M), magnetically stir at room temperature for 2h, let it stand to defoam, and obtain a uniform internal phase solution.
[0070] Example 3
[0071] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that in Example 1, except that: in step (1), SnO 2-x The nanopowder was added to deionized water and dried to prepare a SnO solution with a concentration of 40 mg / mL. 2-xDispersion liquid, add 20mL dispersion liquid and 20mL deionized water in a blue-capped bottle, and add 6.5g PVA and magnetically stir in a water bath at 95℃ for 4h. After cooling, add 1.6mL MB solution (the concentration in the internal phase solution is 0.01M), magnetically stir at room temperature for 2h, let it stand to defoam, and obtain a uniform internal phase solution.
[0072] Example 4
[0073] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that in Example 1, except that: in step (1), 6 g of PHA is dissolved in 94 g of chloroform (CF) to obtain a PHA solution, 22 g of PLA is dissolved in 78 g of dichloromethane (DCM) to obtain a PLA solution, and the PHA solution and the PLA solution are mixed in a volume ratio of 1:5 to obtain an external phase solution.
[0074] Example 5
[0075] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that in Example 1, except that: in step (1), 6 g of PHA is dissolved in 94 g of chloroform (CF) to obtain a PHA solution, 20 g of PLA is dissolved in 80 g of dichloromethane (DCM) to obtain a PLA solution, and the PHA solution and the PLA solution are mixed in a volume ratio of 2:5 to obtain an external phase solution.
[0076] Example 6
[0077] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that in Example 1, except that: in step (1), 6 g of PHA is dissolved in 94 g of chloroform (CF) to obtain a PHA solution, 24 g of PLA is dissolved in 76 g of dichloromethane (DCM) to obtain a PLA solution, and the PHA solution and the PLA solution are mixed in a volume ratio of 2:5 to obtain an external phase solution.
[0078] Example 7
[0079] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that of Example 1, except that in step (2), the collection speed of the fiber collector is 2.4 r / min.
[0080] Example 8
[0081] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that of Example 1, except that in step (2), the collection speed of the fiber collector is 3 r / min.
[0082] Example 9
[0083] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that of Example 1, except that in step (2), the propulsion rate of the internal phase propulsion pump is 0.5 mL / h.
[0084] Example 10
[0085] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that of Example 1, except that in step (2), the propulsion rate of the internal phase propulsion pump is 1 mL / h.
[0086] Embodiment 11
[0087] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that of Example 1, except that in step (2), the propulsion rate of the internal phase propulsion pump is 2 mL / h.
[0088] Example 12
[0089] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that of Example 1, except that in step (2), the propulsion rate of the internal phase propulsion pump is 4 mL / h.
[0090] Embodiment 13
[0091] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber is basically the same as that of Example 1, except that in step (2), the propulsion rate of the internal phase propulsion pump is 5 mL / h.
[0092] The actual pictures of the photochromic PHA / PLA fibers prepared in Example 1 and Examples 9-13 are as follows: Figure 3 shown.
[0093] Embodiment 14
[0094] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber comprises the following steps:
[0095] (1) SnO 2-x The nanopowder was added to deionized water and dried to prepare a SnO solution with a concentration of 40 mg / mL. 2-xDispersion, add 40mL of dispersion to a blue-capped bottle, add 6.5g of PVA, stir magnetically in a water bath at 95°C for 4h, add 1.6mL of MB solution (concentration in the internal phase solution is 0.01M) after cooling, stir magnetically for 2h at room temperature, let stand to defoam, and obtain a uniform internal phase solution. Dissolve 6g of PHA in 94g of chloroform (CF) to obtain a PHA solution, dissolve 20g of PLA in 80g of dichloromethane (DCM) to obtain a PLA solution, and mix the PHA solution and the PLA solution in a volume ratio of 1:2 to obtain an external phase solution.
[0096] (2) Build a microfluidic device. The inner phase circular tube capillary is embedded in the outer phase square capillary, the outer phase square capillary is fixed on the surface of the slide, and then the joint close to the inner phase circular tube capillary is sealed with a dispensing needle to form a microchannel. The inner diameter of the inner phase circular tube capillary is 0.5 mm, and the inner diameter of the outer phase square capillary is 1 mm. The inner phase solution and the outer phase solution in step (1) are respectively loaded into two syringes, and the syringes are installed on the propulsion pump. The inner phase propulsion pump and the inner phase capillary are connected with a polytetrafluoroethylene tube, and the outer phase propulsion pump and the dispensing needle are connected with a polytetrafluoroethylene tube. The port of the outer phase capillary away from the inner phase capillary is immersed in the PEG 400 coagulation bath of the fiber collector, wherein the propulsion rate of the inner phase propulsion pump is 4 mL / h, the propulsion rate of the outer phase propulsion pump is 3 mL / h, and the collection speed of the fiber collector is 4r / min. The fibers collected from the coagulation bath were washed three times with deionized water and air-dried to obtain photochromic PHA / PLA fibers.
[0097] Embodiment 15
[0098] A method for preparing photochromic polyhydroxyalkanoate / polylactic acid (PHA / PLA) fiber comprises the following steps:
[0099] (1) SnO 2-x The nanopowder was added to deionized water and dried to prepare a SnO solution with a concentration of 40 mg / mL. 2-x Dispersion, add 40mL of dispersion to a blue-capped bottle, add 6.5g of PVA, stir magnetically in a water bath at 95°C for 4h, add 1.6mL of MG solution (concentration in the internal phase solution is 0.01M) after cooling, stir magnetically for 2h at room temperature, let stand to defoam, and obtain a uniform internal phase solution. Dissolve 6g of PHA in 94g of chloroform (CF) to obtain a PHA solution, dissolve 22g of PLA in 78g of dichloromethane (DCM) to obtain a PLA solution, and mix the PHA solution and the PLA solution in a volume ratio of 2:5 to obtain an external phase solution.
[0100] (2) The microfluidic chip was replaced with a side-shaft joint coaxial needle (25 / 18 type), the internal phase solution and the external phase solution in step (1) were respectively loaded into two syringes, the syringes were mounted on a propulsion pump, the internal phase solution was injected from the internal phase needle, and the external phase solution was injected from the side-shaft external phase needle, and the fiber was collected using a fiber collector equipped with a PEG 400 coagulation bath, wherein the propulsion rate of the internal phase propulsion pump was 4 mL / h, the propulsion rate of the external phase propulsion pump was 3 mL / h, and the collection speed of the fiber collector was 4 r / min. The fibers collected in the coagulation bath were washed three times with deionized water and dried to obtain photochromic PHA / PLA fibers.
[0101] Test Case
[0102] The mechanical properties of the PLA fiber, the photochromic PHA / PLA fiber prepared in Example 1 and Examples 4-8 were tested by the following method: the fiber sample was cut into 100 mm, and the parts for clamping at both ends of the fiber were marked to ensure that the fiber at the clamping part was in good condition without obvious damage or defects. One end of the fiber sample was fixed in the upper fixture of the mechanical tester to ensure that the fiber was firmly clamped and the clamping part was consistent with the axial direction of the fiber. Then, the other end of the fiber was installed in the lower fixture to make the fiber in a straightened state, and the test speed was set to 20 mm / min.
[0103] The test results are as follows Figure 4 and Figure 5 As shown, from Figure 4 It can be seen that the average breaking strength of pure PLA fiber is 43.6MPa, and the average breaking elongation is 427.6%. With the addition of PHA, the breaking strength and breaking elongation of the fiber are slightly improved. When the volume ratio of PHA solution to PLA solution is 1:5, the average breaking strength of PHA / PLA fiber is 43.9MPa, and the average breaking elongation is 463.7%; when the volume ratio of PHA solution to PLA solution is 2:5, the average breaking strength of PHA / PLA fiber is 48.3MPa, and the average breaking elongation is 481.6%. The above shows that the appropriate addition of PHA in the external phase solution can improve the mechanical properties of PLA fiber, but excessive addition of PHA will affect the fiber spinnability, and will also lead to a decrease in the fiber breaking strength and breaking elongation.
[0104] In addition, when the collection speed is less than 2.4r / min and greater than 4r / min, the fiber cannot be formed well. Figure 5It can be seen that when the collection speed is 2.4r / min, the average breaking strength of the fiber is 10.4MPa, and the average breaking elongation is 430.1%; when the collection speed is 3r / min, the average breaking strength of the fiber is 13.7MPa, and the average breaking elongation is 430.4%; when the collection speed is 4r / min, the average breaking strength of the fiber is 17.6MPa, and the average breaking elongation is 430.6%. It can be seen that with the increase of the collection speed, the breaking elongation of the fiber does not change significantly, but the breaking strength of the fiber increases significantly. This is because the external force is conducive to the orientation of the polymer macromolecular chain, the amorphous structure in the PLA fiber tends to be arranged regularly, and the orientation increases to induce crystallization, and the orientation recrystallization of the molecular chain along the force direction will occur. Moreover, with the increase of the collection speed, the multiple of the fiber drafting increases, the degree of fiber orientation increases, and the macromolecular chain is arranged regularly. Therefore, when subjected to external force, the fiber breaking strength is improved.
[0105] The changes of the photochromic PHA / PLA fibers prepared in Examples 1-3 under blue light (400-480nm) were tested by using a spectrophotometer to measure its Lab and Yxy data, the measurement wavelength range of the spectrophotometer being between 400nm and 700nm, and preferably using a D65 light source. The photochromic PHA / PLA fiber sample was placed flat on the measurement platform to ensure that the sample surface was flat and closely fitted to the measurement port to avoid gaps or wrinkles that would affect the accuracy of the measurement results, and the reflection mode was used to measure the changes in the surface color under different lighting conditions.
[0106] The test results are as follows Figure 6 , Figure 7 and Figure 8 As shown, the test data of Lab and Yxy are shown in Table 1:
[0107] Table 1
[0108]
[0109] The sample made of photochromic PHA / PLA fiber prepared in Example 1 fades under blue light (400-480nm) and recolors under red light (625-665nm) as shown in the figure. Fig. 9 shown.
[0110] Fig.10The test results of the inner phase solution in Example 15 under light irradiation are shown in Figure 15; (a) is a physical picture of the inner phase solution fading under green light (500-550nm) and recoloring under red light (625-665nm), (b) is a UV absorption spectrum of the inner phase solution, and (c) is a graph showing the change in absorption intensity at 662nm after 10 cycles of alternating UV light (365nm) and red light irradiation. Fig.10 As can be seen in (b), the two absorption peaks of MG at 612nm and 662nm gradually decreased and disappeared completely, indicating that ultraviolet light and red light can effectively fade and restore the corresponding internal phase solution. Fig.10 As can be seen in (c), during multiple cycles, the color-changing system is also proven to have excellent repeatability and reversibility. However, as the number of color conversion reactions increases, the absorption spectrum intensity decreases to a certain extent due to the accumulation of photodegradation side reactions.
[0111] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A photochromic polyhydroxyalkanoate / polylactic acid fiber, characterized in that: The photochromic polyhydroxyalkanoate / polylactic acid fiber has a skin-core structure, and the core layer material includes a polymer, a dye, and SnO 2-x , where 0 < x < 0.5, and the polymer is polyvinyl alcohol and / or cellulose; the skin layer material includes polyhydroxyalkanoate and polylactic acid.
2. The photochromic polyhydroxyalkanoate / polylactic acid fiber according to claim 1, characterized in that: The dye is selected from one or more of methylene blue, methylene green and neutral red.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the polyhydroxyalkanoate to polylactic acid is (5-20):(100-120).
4. A microfluidic device, characterized in that: include: An internal phase propulsion pump, used to propel the internal phase solution; An external phase propulsion pump, used for propelling the external phase solution; Glass slides; A dispensing needle, which is located at the end of the external phase capillary tube away from the fiber collector and is used to connect the internal phase capillary tube and the external phase capillary tube; An inner phase capillary, part of which is embedded in the outer phase capillary and is used for transporting the inner phase solution; an external phase capillary, which is fixed on the surface of the glass slide and is used to transport the external phase solution; as well as The fiber collector is used to collect the fibers formed after the interaction between the inner phase solution and the outer phase solution.
5. A method for preparing photochromic polyhydroxyalkanoate / polylactic acid fiber, characterized in that: The method of preparing photochromic polyhydroxyalkanoate / polylactic acid fiber by using the microfluidic device according to claim 4 comprises the following steps: Dissolve the core layer material in a solvent to obtain an internal phase solution. The core layer material includes a polymer, a dye, and SnO 2-x , where 0 < x < 0.5, and the polymer is polyvinyl alcohol and / or cellulose. Mix the polyhydroxyalkanoate solution and the polylactic acid solution to obtain an external phase solution. Use an internal phase pump to push the internal phase solution into an internal phase capillary, and use an external phase pump to push the external phase solution through a dispensing needle into an external phase capillary. A coagulation bath is installed in the fiber collector, and the photochromic polyhydroxyalkanoate / polylactic acid fiber is collected in the coagulation bath.
6. The preparation method according to claim 5, characterized in that: The concentration of the polymer in the inner phase solution is 10-17 wt %, the concentration of the dye in the inner phase solution is 0.01-0.05 M, and the concentration of SnO in the inner phase solution is 0.01-0.05 M. 2-x The concentration is 30-100 mg / mL.
7. The preparation method according to claim 5, characterized in that: The volume ratio of the polyhydroxyalkanoate solution to the polylactic acid solution is (1-3):
5.
8. The preparation method according to claim 5, characterized in that: The propulsion rate of the inner phase propulsion pump is 3-5 mL / h.
9. The preparation method according to claim 5, characterized in that: The coagulation bath is polyethylene glycol and / or ethanol.
10. Use of the photochromic polyhydroxyalkanoate / polylactic acid fiber according to any one of claims 1 to 3 or the photochromic polyhydroxyalkanoate / polylactic acid fiber prepared by the method according to any one of claims 5 to 9 in the field of textiles.
Citation Information
Patent Citations
Photochromic polyester fiber with sheath-core structure
CN110629319A
Microfluidic spinning construction method of high-strength spiral fiber
CN113913956A